THE FOOTSTEPS OF RESISTANCE IDEOLOGY IN MANGKUNEGARAN DANCE-STYLE - Widodo Aribowo; Andrik Purwasito; Titis Srimuda Pitana (Proceeding IICACS, 2019)
This study aims to describe the ideology of resistance that grew and became the basis of the politics of cultural movement during the war to the establishment of Puro Mangkunagaran up to maintainaning the existence to the present. The study was descriptive analytic using 12 advanced-steps method of Spradley Ethnography, which was shortened into 4 research steps. Triangulation data research includes direct observation of Bedhaya Anglir Mendhung dance performance, dance manuscripts in Mangkunagaran, and interviews with two respondents. The findings of this study are: a) dance art in Puro Mangkunagaran are all themed with resistance except free-patterned dance like gambyong and golek; b) Bedhaya Anglirmendhung dance is the first Puro Mangkunegaran‘s Bedaya dance as well as an attribute of power in which ideologically articulates resistance;c) the ideology of resistance is also evident in the archetypal orstate logo artefacts, batik cloths, and the family of Mangkunagaran creeds.Keywords: ideology; representation; Mangkunagaran